Interpreting the lament Psalms from the Tanzanian context: problems and prospects - Boniface-Malle, Anastasia (Luther Seminary, 2000)
The Lament Psalms are among the Old Testament texts that do not have much influence and impact for the Christians of the Evangelical Lutheran Church in Tanzania. This is due to the inherited Western Christian traditions which regarded complaints to be incompatible with the Christian faith. As a result, the Tanzanian Church has overlooked and failed to integrate two of her religious heritages in prayer and worship. I contend that the devaluation and absence of the Lament Psalms stem basically from the lack of proper interpretations of these texts. The flaws and distortions in interpretation have censured these psalms from the practical life of the Church. This study seeks to bridge the gap and to bring harmony between the Lament Psalms and the Church practices. The gap Gan be bridged through effective interpretation of the Lament Psalms. The effective reading in this thesis is doing a close reading of the Lament Psalms, that is, reading the biblical laments in conjunction with African lament traditions. In this research, five Psalms of Lament have been critically examined in conjunction with African lament songs. This critical analysis comes immediately after the introductory chapter. The emphasis has been on translations, close readings, literary contexts, and central theological themes for each Psalm. Chapter three concentrates on the broader theological motifs of the Lament Psalms, and examining how these motifs relate to the rest of the Lament Psalms. Chapter four introduces the reading of the Lament Psalms in the Tanzanian context. This includes the study of the traditional lament prayers, an investigation of the worship material in the ELCT, and the use of the biblical Psalms in the life of the Church. Hermeneutical implications of this study are deliberated in chapter five, where the problems and prospects of such interpretation are emphasized. Tanzanian lament songs and traditions pose several significant elements that can enhance and illuminate our reading of the Psalms of Lament. Among these, aspects such as community, rituals, and language need to be considered in order to read effectively the Lament Psalms in a given cultural context. Finally, the thesis concludes by arguing that any anthropologically and culturally sound theology has to take into account the people's experience, in a way that they can grasp and integrate culture and their new faith.
paid
Keywords: Academic Dissertation; Academic theses; Bible. Psalms; Bible. Psalms Criticism; interpretation; etc; Christianity; Christianity Tanzania; Criticism; interpretation; etc; Lamentations dans la Bible; Laments in the Bible; Tanzania; Thèses et écrits académiques